Penerapan Metode Simple Additive Weighting (SAW) dalam Sistem Pengambilan Keputusan Order Persediaan Barang Berbasis Web - Iin Marliana (Sienna, 2020)
Nowaday, computers already can be used to provide choices in taking of the decision, not only used for data processing or presenting information, process of taking the decision it self is the results of a system that called Sistem Pendukung Keputusan (SPK). The system of taking the decision is possible because there has been a development of hardware technology, integration of hardware and software. In the business sector one of them is a truck and expedition which engages in the transportation services of stuffs between Lampung-Surabaya cities and vice versa. In this expedition service consists of arround used by 76 units of cars. And the supply of stuffs still used bookkeeping which is sometimes taking of the decision supply of stuffs is still handled by superiors. Therefore, this research used Simple Additive Weighting (SAW) method which is used to make decisions in problems solving by create a design system and building software. This research will create a system when taking the decision in the supply of stuffs in the Business Entity Expedition Services with SAW method by using WEB.